Coherent perfect absorption in the one-dimensional non-magnetized plasma photonic crystals. (15th December 2021) - Wu, Fupei; Zhang, Hao; Wan, Baofei; Zhang, Haifeng
Abstract: Electromagnetic (EM) absorption is the basic characteristic of materials that plays an important role in many applications such as solar cells, EM radiation protection, and stealth technology. However, under normal circumstances, the traditional medium's absorption efficiency of EM waves is limited, but the designer can operate by adjusting the structure of the medium. In this paper, the coherent perfect absorption (CPA) is introduced in the one-dimensional (1D) non-magnetized plasma photonic crystals. Under the premise that the selected material meets the conditions (appropriate thickness and dielectric constant), the absorption amplitude at the frequency point that meets the coherent absorption conditions is greatly improved. The results show that the forward and backward EM waves that meet the CPA conditions and propagate in PPCs can increase the absorption to 99.94% and change the phase difference of the two coherent beams to control the adjustment range of the absorption efficiency to 12.60%–99.94%. In addition, the effects of plasma and collision frequency on the absorption property, and the effects of the periodic constant of dielectric layers and plasma thickness on the frequency and amplitude of coherent absorption are also presented. It is foreseeable that the idea of tunability of light absorption in photovoltaic cells is proposed in this paper, and the application of absorbers in the field of optical switching and light modulation has been further expanded.